Archaeological Activity in Palestine and Transjordan in 1941-1942 - Glueck, N.
Palestine: Prehistoric Archaeology — Transjordan: Prehistoric Archaeology — Palestine: Early Historic Archaeology — Transjordan: Early Historic Archaeology.